Periodontal disease increases the risk of severe pre-eclampsia among pregnant women - Varol Canakci (Blackwell Synergy, 2007)
Aim: To evaluate the possible link between the severity of periodontal disease and pre-eclampsia and to correlate this link to clinical periodontal parameters and interleukin (IL)-1b, tumour necrosis factor-a (TNF-a), and prostaglandins (PGE2) levels in both gingival crevicular fluid (GCF) and serum. Material and Methods: Fifty-nine pregnant women (20 mild pre-eclampsia, 18 severe pre-eclampsia, and 21 healthy pregnant women) were included in the study. Dental and periodontal recordings as well as GCF and blood samples were obtained within 48 h preceding delivery. Results: The results of multivariate logistic regression showed a highly significant association between mild to severe pre-eclampsia and severe periodontal disease (po0.001). After adjusting for potential confounders (smoking, body weight, socioeconomic status, education level, and age), severe pre-eclamptic women were 3.78 (1.77–12.74) times more likely to present severe periodontal disease than normotensive pregnant women. This odds ratio (OR) was 2.43 (1.13–8.19) for mild pre-eclamptic women. IL-1b, TNF-a, and PGE2 levels in both serum and GCF were also significantly higher in the pre-eclamptic groups than the normotensive women. Conclusions: These results indicate that the presence and severity of periodontal disease seems to increase the risk for not only the occurrence but also the severity of pre-eclampsia in pregnant women.